The Colossus of New York, de Colson Whitehead, petite topographie poétique - Sylvie Bauer (Anglophonia)
The Colossus of New York, by Colson Whitehead, refuses categorization: neither a novel nor a documentary text, it provides the reader with a poetic experience of New York, opening windows onto a myriad fragments of lives in a somewhat enchanted place, both extremely familiar and made uncanny through language. The well-known, mythical places of the city and its clichés are re-worked by the collisions of words and sounds which transform both city and text into chimeras, thus raising the question of meaning. In the end, if meaning does escape the grips of the reader, it nonetheless prompts an attempt at recapturing a supposedly blissful past through the workings of memory and the rehabilitation of cliché as the trace of the lost event.